STRATEGI KOMUNITAS TRADITIONAL GAMES RETURNS (TGR) DALAM PELESTARIAN PERMAINAN TRADISIONAL PADA ANAK USIA 7-12 TAHUN: Studi Kasus di RW 03, Kelurahan Cakung Timur, Kecamatan Cakung, Kota Jakarta Timur - Kartiningsih, Kartiningsih; Budiaman (Edukasi IPS, 2020)
This study aims to identify the causes of children aged 7-12 years who are currently less interested in traditional games, then what is the strategy done by the TGR Community in preserving traditional games for children aged 7-12 years to be interested, and change is happens to children aged 7-12 years after the action from the TGR Community. Research carried out using a type of qualitative research with a case study method. Data collection techniques are carried out, namely, interviews, observation, document analysis, and field notes. Document analysis techniques used are data reduction, data presentation, and conclusion. The results of this study conclude that: The causes of children aged 7-12 years are less fond of traditional games due to inadequate physical conditions of the environment, the role of parents who are not guiding their children to play traditional games, as well as people's mindsets and times that make traditional games considered no longer interesting compared to digital games on the device. Then the strategy carried out by the TGR Community is to restore the existence of traditional games to children by going through three stages, including formulation, implementation, and evaluation. Changes that occur after the actions carried out by the TGR Community, namely children no longer tend to play the device, although not a few of them are difficult to release the device and replace digital games with traditional games, but they have made traditional games as an alternative to the games in the device.